Revisiting Microleakage: Persistent Challenges in Restorative Dentistry - Malempati, Raja Rajeswari; Konakanchi, Anusha; Ganta, Gopala Krishna; Vangala, Ramalakshmi Manogna; Alla, Rama Krishna; Mohammed, Shammas (International Journal of Dental Materials, 2025)
The infiltration of fluids, bacteria, and ions at the interface between dental restorations and tooth structure remains a persistent challenge in restorative dentistry, significantly impacting the longevity and clinical success of restorations. This review comprehensively examines the factors contributing to microleakage, evaluates various detection methodologies, and explores strategies to mitigate its adverse effects. Emphasizing an evidence-based approach, the review highlights key considerations in restorative techniques, material selection, and adhesive protocols that enhance marginal integrity. By synthesizing current research and clinical recommendations, this article provides practical guidance for clinicians to minimize microleakage and improve the durability of dental restorations.